The Credit Hour System As Adapted by the University of Gezira: Special Reference to Medical Faculties - Adam, Hussein S. (Gezira Journal of Health Sciences, 2005)
The University of Gezira was established in 1975. The first Batch of students registered for their first semester in September 1978. There were four Faculties at that time: Agricultural Sciences, Economics & Rural Development, Medicine and Science & Technology (Presently Engineering & Technology). There were about 50 students in each Faculty. The teaching was in English. The pioneers opted for a modified American System rather than having a carbon copy of the University of Khartoum with its well established British System. They chose the Credit Hour System adapted to Sudanese environment.